Growth and development of journalism in the United States - Wilson, Alexander George (My University, 1899)
Introduction: In this production, the writer will endeavor to trace the growth and development of journalism in the United States, from the time of its beginning up to the present century; and to make brief mention of some of the men who have held places of prominence in this profession. The importance of the press, and the high position it holds today, together with the prominence to which many men have risen in the journalistic field, are my reasons for choosing this subject. The newspaper today is the power of the world; it molds public opinion, and its influence cannot be over-estimated. The one great mission of the press is to elevate humanity. With growth in power, the press has been accompanied by an increase of responsibilities. This production has been written after research and study of some of the most noted writers on the subject of journalism. The opinions of different journalists have been taken in part, and presented here in a condensed form, together with the ideas held by the writer. The broadness of the subject makes it almost impossible for one to do justice to it.
Citation: Wilson, Alexander George. Growth and development of journalism in the United States. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Importance of Early Papers; Newspaper of the West; Special Journalism; Theses; Manuscripts (documents)